PERAN AKUNTANSI SYARIAH DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS DI PT. BPRS HAJI MISKIN - Andini Amalia Putri SW; Iwan Setiawan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study explores the role of sharia accounting in enhancing transparency and accountability at PT. BPRS Haji Miskin. Employing a descriptive qualitative approach, primary data were collected through interviews, observation, and documentation involving managers and accounting staff. The findings show that the implementation of the Statement of Financial Accounting Standards for Sharia (PSAK Syariah) and guidelines from the National Sharia Council (DSN-MUI) in the process of recording and reporting sharia-based financing supports transparent and accountable financial administration. However, there are notable challenges, such as limited human resources with in-depth understanding of sharia accounting and the difficulties of integrating information technology systems. Efforts to improve transparency and accountability are carried out through intensive training, collaboration with regulators, and the digitization of accounting systems. The results of this research are expected to contribute to the development of better and more sustainable sharia financial governance practices in Indonesia’s sharia banking sector.